Futures imaging: student views, mediation and learning through science - Lloyd, David G. (Curtin University, 2002)
The thesis presents a critique of the nature of 13 to 15 year-old students' images of futures. Arguments are made for their importance to the individual community and culture and their value and use in a science learning setting.This study of the nature of futures images is based upon data collected from small samples in two school settings between 1990 and 1999 using a guided fantasy approach. The diversity of student hopes and fears for futures is categorised using several research tools developed from the futures literature. The results identify a range of futures scenarios ranging from highly utopic to highly dystopic and themes including human interactions, the natural and built environment and the nature and use of futuristic technologies.The importance of student images of futures is discussed from the personal perspective of the students and then considered in the broader context of society and Western culture. The data are examined through a number of theoretical frames including psychology, history and the futures field of enquiry. The consensus seems to be that expectations of the future are inseparable from human nature and influential in determining the viability of cultures.The value of student images of futures in science learning is explored through a case study of one of my own Year 9 classes. In teaching this class I used the technique of futures imaging integrated into a critical futures teaching approach utilising a constructivist planning model. I found that students' futures images revealed a broader aspect of student worldviews than is usual in science learning environments, and were valuable in exposing student prior knowledge, interests and concerns. Student learning seemed to be enhanced using this futures oriented approach.